Anti-Thermal Shock Binding of Liquid-State Food Waste to Non-Wood Pellets - Almeida Moreira, Bruno Rafael de [UNESP]; Viana, Ronaldo da Silva [UNESP]; Cruz, Victor Hugo [UNESP]; Matos Lopes, Paulo Renato [UNESP]; Miasaki, Celso Tadao [UNESP]; Magalhaes, Anderson Chagas [UNESP]; Monteiro de Figueiredo, Paulo Alexandre [UNESP]; Manzani Lisboa, Lucas Aparecido [UNESP]; Ramos, Sergio Bispo [UNESP]; May, Andre; Caraschi, Jose Claudio [UNESP] (Mdpi, 2020)
The development and implementation of strategies to assist safe and effective transport and storage of pellets in containers and indoor facilities without heating systems are challenging. This study primarily aimed to reshape the organic fraction of municipal solid waste into a liquid-state binder in order to develop freezing-defrosting-proof non-wood pellets. The introduction of the standard solution of food waste into the process of pelleting consisted of stirring it together with the residual biomass from distillation of cellulosic bioethanol or alternatively spraying very fine droplets on the layer of the starting material before it entered the pilot-scale automatic machine at 200 MPa and 125 degrees C. The addition by spraying of carbohydrate-rich supplement boiled for five minutes caused the pellets to show increases in apparent density (1250.8500 kg center dot m(-3)), durability (99.7665%), and hydrophobicity (93.9785%), and consistently prevented them from suffering severe mechanical fracture by thermal shock. The fractal dimension of breakpoints, cracks, and delamination on the finished surface for these products was the smallest at 1.7500-1.7505. Sprayed pellets would fall into the strictest grid of products for residential heat-and-power units, even after freezing and defrosting. The conclusion is therefore that spraying can spectacularly ensure the reliability of liquid-state food waste as an anti-thermal shock binder for non-wood pellets.
Keywords: agro-industrial residue; defrosting; durability; fractal analysis; fractures; freezing; storage; municipal solid waste; transportation; waste-to-energy